Green innovations in third-party logistics: Managerial reasons, external stakeholder influences and contingencies in the natural-business environment - Bálint, M.; Vilas-Boas da Silva, J. M.; Möhring, M. M. (Cogent Business and Management, 2025)
Increasing ecological consciousness makes adopting green innovations a strategic concern for third-party logistics providers (3PLs). This article addresses gaps in understanding how 3PLs can strategically leverage green innovations and the business environment characteristics influencing their adoption through a multiple-case study of six environmentally proactive German 3PLs using semi-structured interviews and triangulated with secondary data. Results show varied adoption levels with process innovations linked to cost savings, enhanced reputation and long-term energy independence. Large 3PLs differentiate through green services in eco-aware segments. Moreover, findings highlight the importance of managing external stakeholder relationships and reveal market-related contingencies that create uncertainty and complexity for 3PLs, such as unpredictable technological developments or shifting governmental regulations. Market munificence plays a crucial role in enabling green innovation adoption, with small-/mid-sized 3PLs facing challenges in accessing external green knowledge and personnel. This study is informed by the Natural Resource-based View (NRBV), Stakeholder Theory (ST) and Contingency Theory (CT) perspectives, developing a comprehensive framework that coherently structures the problem-situation and derives propositions for subsequent explanatory investigations. It recommends a step-by-step approach to green innovations, forming diverse partnerships and maintaining communication with shippers to overcome perceived market-related contingencies. Small-/mid-sized 3PLs should consider horizontal cooperation for unified advocacy and shared best practices.